2001
DOI: 10.1128/aem.67.9.3904-3907.2001
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Fomites in the Vehicular Transmission of Human Astroviruses

Abstract: The persistence of human astroviruses dried on representative porous (paper) and nonporous (china) surfaces was investigated. Long-term astrovirus survival on fomites was monitored by an integrated cell culture-reverse transcription-PCR procedure. Viruses were applied to inanimate surfaces in the presence and absence of fecal material, and their survival was assayed at 4 and 20°C with high relative humidity. Astroviruses exhibited a notable persistence when dried on porous and nonporous materials, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 25 publications
0
67
0
1
Order By: Relevance
“…Several large HAstV outbreaks have been associated with consumption of contaminated food (205)(206)(207). In addition, fecally contaminated fomites have been implicated in outbreaks declared in institutions such as day care centers, hospitals, nurseries, schools and military facilities (208,209). Moreover, waterborne transmission of HAstVs has been suggested as a risk of digestive morbidity for the general population (210), and HAstV was recovered in surface water from an area in which an outbreak of gastroenteritis was concomitantly occurring (211).…”
Section: Epidemiology Hastv Transmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several large HAstV outbreaks have been associated with consumption of contaminated food (205)(206)(207). In addition, fecally contaminated fomites have been implicated in outbreaks declared in institutions such as day care centers, hospitals, nurseries, schools and military facilities (208,209). Moreover, waterborne transmission of HAstVs has been suggested as a risk of digestive morbidity for the general population (210), and HAstV was recovered in surface water from an area in which an outbreak of gastroenteritis was concomitantly occurring (211).…”
Section: Epidemiology Hastv Transmissionmentioning
confidence: 99%
“…This seasonality may be the consequence of a better stability of the virus at lower temperatures (208,212). Other viral gastroenteritis agents such as rotaviruses and noroviruses, but not adenoviruses, show a similar seasonal pattern (258)(259)(260).…”
Section: Age Geographic and Temporal Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bodily fluids such as saliva, mucus, nasal secretions, blood, urine, and feces may all potentially contain pathogens that can be transmitted via fomites (6)(7)(8)(9). A number of studies have shown that enteric and respiratory pathogens are capable of surviving from hours to months on fomites, depending on the numbers deposited, the type of microorganism, and the variable environmental conditions (10)(11)(12). Several studies have shown that inanimate surfaces found in day care centers (8,(13)(14)(15)(16)(17), schools (18), office buildings (19), homes (20)(21)(22)(23)(24)(25)(26)(27), public areas (28), or hospitals (12,(29)(30)(31)(32)(33) can be reservoirs for secondary modes of transmission, with contaminated hands playing a critical role as a route of exposure.…”
mentioning
confidence: 99%
“…Therefore, there is increasing public interest in examination of microbiological contamination of fomites in community settings. Some microorganisms can be pathogenic at low concentrations and survive on nonporous surfaces such as telephones, taps, doorknobs and toilet bowls (Goldmann, 2000;Abad et al, 2001;Rusin et al, 2002;Reynolds et al, 2005). There are few data available concerning the investigation of bacterial pathogens from public telephones (Ferdinandus et al, 2001;Tunç and Olgun, 2006;Annand et al, 2009;Brooke et al, 2009).…”
Section: Introductionmentioning
confidence: 99%